CFD Simulation of Gas–Solid Mixing in a Spouted Bed Applied to the Conversion of Polyolefin Waste - Inacio; Renata; Renato; Daniel; Marcelo (Latin American Journal of Energy Research, 2025)
Pyrolysis in spouted bed reactors can recover aluminum and produce waste-derived fuel from carton packages. However, reactors with polyethylene/aluminum composite (LDPE/Al) and sand mixing (of different sizes and specific densities) can lead to unstable spouting regimes. Therefore, this research aims to simulate the gas-solid flow in beds with mixtures of sand and LDPE/Al using a 2D Euler-Euler Granular model. This allows for the identification of stable operational conditions with low particle segregation. Results show that the mixing index predictions agree with experimental data. Predicting the effect of operating conditions and mixture properties on the degree of bed mixing aids in the start-up of pyrolysis reactors for producing waste-derived fuels and aluminum recovery.